Enterprise Social Networks as a Meeting Tool in the Czech Republic - Školudová, Jana (My University, 2016)
Meetings are an essential prerequisite for successfully communicating and transferring internal information. The question is whether or not businesses in the present day are organizing and leading meetings effectively. The goal of this paper is to conduct a comparison of the requirements for effective meeting leadership with the current state of businesses in the Czech Republic. Furthermore, the paper aims to answer a research question relating to the feasibility of using enterprise social networks for conducting company meetings. The goal of the survey research was to map the current state of the investigated problematic and its trends. The paper's methodology is based on managed interviews conducted in 2014. An overall comparison of the data that was acquired shows the current trends and points to a discrepancy between the requirements for conducting meetings and reality. The results indicate the possible use of modern technologies for more effectively conducting meetings within businesses in the form of enterprise social networks. The paper discusses the use of the latest trends and innovations concerning technologies that help managers effectively transfer internal information; it also outlines a concept for further research directions. The paper attempts to emphasize the fact that it is necessary to pay attention to modern technologies and embrace new, sophisticated tools for ensuring effective meeting leadership.
Podnikové sociální sítě jako nástroj pracovních porad v ČR
Keywords: management; information technology; human resource management; enterprise social network; meeting; organization; management; informační technologie; řízení lidských zdrojů; podniková sociální síť; porada; organizace